Preparation of induced pluripotent stem cells on dishes grafted on oligopeptide under feeder-free conditions - Higuchi, Akon; Lin, Feng Ling; Cheng, Yu Kai; Kao, Ta Chun; Kumar, S. Suresh; Ling, Qing Dong; Hou, Chun Han; Chen, Da Chung; Hsu, Shih Tien; Wu, Gwo Jang (Elsevier, 2014)
Human embryonic stem cells (hESCs) and human induced pluripotent stem cells (hiPSCs) have potentially therapeutic applications in the treatment of many diseases, due to their unique ability to differentiate into any type of somatic cell. However, the clinical potential of hESCs and hiPSCs is restricted by the use of mouse embryonic fibroblasts (MEFs) as a feeder layer for these cells. We report that hiPSCs can be successfully generated without the use of a feeder layer of MEFs. We generated hiPSCs by transducing human adipose-derived stem cells (hADSCs) with a retrovirus containing pluripotency genes, and the hiPSCs were cultured on synthetic dishes grafted with an oligopeptide derived from vitronectin (VN-dish). On the fourth day after transduction, the hADSCs transduced with pluripotency genes were transferred to a MEF layer for culturing as a control condition or to VN-dishes for culture. The hiPSC colonies in the MEF-cultures were clearly observed at day 14 after transduction, whereas hiPSC colonies were detected on the VN-dishes after the cells were passaged. When 105 hADSCs were seeded on the dishes, the number of colonies generated on the MEFs was 120 ± 28, while the number of colonies generated on VN-dishes was 25 ± 8. Thus, the efficiency of hiPSC generation on the VN-dishes under feeder-free conditions was lower than hiPSCs cultured on MEFs. However, the hiPSC colonies from VN-dishes demonstrated alkaline phosphatase activity, and immunohistochemistry suggested that the hiPSCs generated on VN-dishes expressed the pluripotency protein, stage-specific embryonic antigen-4 (SSEA-4), under feeder-free conditions.